Makna Logos dan Logika dalam Yohanes 1:14 bagi Pertumbuhan Iman Kristen Masa Kini - Josapat Bangun; Suhadi Suhadi (Jurnal Teologi Berita Hidup, 2023)
Today's Christian faith is mostly built without Logos and logic, as a result there is a deviation of faith growth, not towards Christ as the Head of the Church, but growing towards faith in oneself, faith in material things, faith in miracles, and faith without a solid foundation. Many studies on the Logos have been done, as well as on logic, especially in philosophy. However, the study of the meaning of Logos and logic associated with the growth of Christian faith with qualitative methods is something new, the results are expected to add to the treasures of academic scientific literature. It turns out that the growth of Christian faith will not occur in a healthy and balanced manner if only through reading the Logos alone and also if only relying on limited logic. The growth of Christian faith is very dependent on the balance of studying the Logos as a Person and the graphe Logos critically and analytically by using the logic of God's gift properly and correctly, in the help, guidance, and being led by the Holy Spirit. As it turns out, the growth of true Christian faith only occurs if the Logos and Logos become the leading subject, while logic becomes a limited instrument that must always thirst and hunger for true truth. Always realize that the logic that has been updated must always be subject to the guidance of the Holy Spirit so as not to go astray. All learning outcomes to the Logos and Logos should be realized in concrete actions (operibus) as a sign of faith growth and spiritual maturity in the Logos, the goal is that the growth of Christian faith has a significant impact on the world where Christian faith is present as a manifestation of the incarnation of the Logos in the Logos. believer's life today.